Membangun Imajinasi Kreatif Anak Melalui Kegiatan Seni Rupa Anak Usia Dini Dengan Teknik Tempel Menggunakan Cotton Bud - Hasanah, Yuniatun; Hidayatu Munawaroh (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2024)
Fine art is a learning medium that gives children the freedom to be creative, so that it can build the imagination and creativity of young children. The aim of the research is to describe the role of fine arts learning in building the imagination and creativity of PAUD Al-Madina Kaliwiro children through playing with cotton buds. The research method uses qualitative methods with observation, interviews and documentation. This game is implemented by children sticking several cotton buds on a piece of paper. The results obtained from this research are that the game of sticking cotton buds works well which is in accordance with the characteristics of the independent curriculum and this game is used as learning to develop children's imagination and creativity.